2020
DOI: 10.5213/inj.2040186.093
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations of Overactive Bladder With Migraine as a Comorbidity: A Prospective Cross-Sectional Study

Abstract: Purpose: The aim of this study was to investigate the clinical manifestations of overactive bladder (OAB) with migraine as a comorbidity and to shed light on possible new treatment strategies.Methods: This study included patients aged 18 years and older who were admitted to urology and neurology outpatient clinics between March 1, 2019 and March 1, 2020 for OAB and migraine. The study questionnaire contained 3 sections: (1) questions on demographic characteristics, (2) a migraine ID test, and (3) the Overactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Many conditions, including temporomandibular joint disorders, fibromyalgia, chronic fatigue syndrome, headache, complex regional pain syndrome, and IBS, are defined as syndromes associated with CS. 5 It is known that nonurological symptoms are more common in OAB patients than in the general population. Previous studies have found that OAB frequently occurs together with different types of headaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many conditions, including temporomandibular joint disorders, fibromyalgia, chronic fatigue syndrome, headache, complex regional pain syndrome, and IBS, are defined as syndromes associated with CS. 5 It is known that nonurological symptoms are more common in OAB patients than in the general population. Previous studies have found that OAB frequently occurs together with different types of headaches.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, CS is explained to contribute to the pathophysiology of functional somatic syndromes, somatoform disorders, medically unexplained conditions, and chronic pain. 4,5 It has also been reported that patients with CS experience altered pain perception, decreased pain threshold, referred pain, and allodynia, and that there is psychosocial impact and QoL is affected. 4 Multiple possible mechanisms have been reported in the pathophysiology of OAB, including myogenic, neurogenic, and idiopathic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods and learning algorithms for motion recognition have been proposed. Most studies have used static algorithms such as ANNs ( Karmonik et al, 2019 ; Kim et al, 2020 ; Nikkola et al, 2020 ; Prabhakar et al, 2019 ) and K-means clustering ( Baser et al, 2020 ; Fraley and Raftery, 2002 ; Moon and Cho, 2021 ), or dynamic time warping ( Powar and Chemmangat, 2019 ) in combination with algorithms. However, a time series algorithm should be used to predict or classify dynamically changing time series data.…”
Section: Application Of Artificial Intelligence In Urological Settingmentioning
confidence: 99%
“…Although many methods are used in the treatment of OAB, fluid intake modification, restriction of caffeine and tea, weight reduction, bladder training, which constitute behavioral therapy, are recommended in the first-line treatment. Furthermore, in addition to behavioral therapy, pelvic floor muscle training (PFMT) and antimuscarinic and/or beta3-agonist therapy may be implemented in the first-line treatment [5,6]. Patients who were nonrespondent to the first-line treatment may undergo therapeutic methods such as intravesical botulinum toxin administration, posterior tibial nerve stimulation, and sacral neuromodulation [7].…”
Section: Introductionmentioning
confidence: 99%